New Pireninae (Hymenoptera: Pteromalidae) from South-East Asia - Mitroiu, Mircea-Dan (Zootaxa, 2011)
Keesia Mitroiu, gen. nov. is described for K. dorsellata Mitroiu, sp. nov. (type species) and K. tripotini Mitroiu, sp. nov. Also described and illustrated are Zebe darlingi Mitroiu, sp. nov., Z. tabiwah Mitroiu & Darling, sp. nov., Macroglenes kuwatus Mitroiu, sp. nov. and M. sulawensis Mitroiu, sp. nov. All species except K. tripotini, collected in South Korea, and Z. tabiwah from Malaysia (Sarawak), were collected in Indonesia. These are the first records of the subfamily Pireninae in Indonesia and South Korea.